Analysis of the Institutions Role in Sustainable Domestic Wastewater Management in Jakarta - Wirawan, Sri Mahendra Satria; Maarif, Mohamad Syamsul; Riani, Etty; Anwar, Syaiful (Research and Development Agency Ministry of Home Affairs, 2018)
Currently, the Jakarta water is suffering from a high level of pollution, both the groundwater or the river. This is mainly caused by domestic wastewater disposal that has not been properly controlled. Efforts to develop domestic wastewater management are inadequate. Infrastructure development is very slow, the community participation and care, the wastewater management competencies and capacities are all very low. For this reason, it is necessary to increase the role of domestic wastewater management operators and regulators, to accelerate the construction of domestic wastewater treatment infrastructure, improve the participation and care of the community, and to improve the competence and capacity of domestic wastewater management service managers. The purpose of this study was to determine the role of the operators and regulators in the development of domestic wastewater management in DKI Jakarta. To achieve this goal, this study was conducted using the method of interpretive structural modeling (ISM) as a method for analyzing the interrelationships between institutions in the framework of developing domestic wastewater management. The result of this study shows that the key institutions that could accelerate the wastewater infrastructure development are the Coordinating Ministry of Economic Affairs, National Development Planning Agency, and the Ministry of Public Works and Public Housing. The key institutions in enhancing the participation and care of the community are the Water Resources Office, the Environmental Office and the regional owned company Managing DKI Jakarta Waste Water. The key institutions related to improving the competence and capacity of domestic wastewater service managers are the Ministry of Public Works and Public Housing.